Financed homeownership and the economic downturn in South Africa. (December 2015) - Marais, Lochner; Cloete, Jan
Abstract: Urban South Africa has seen a transformation to homeownership since the mid 1980s, achieved mainly through the restoration of urban homeownership rights and property rights. Ownership has been transferred to some 500, 000 state rental low income households and a capital subsidy scheme has assisted approximately three million low income households since the early 1990s. At the same time mortgage finance became available to black households during the mid 1980s. Since the mid 1980s, a concerted effort was made to increase housing finance to the historically disadvantaged black population of South Africa. Drawing on a policy assessment and the panel National Income Dynamics Study, we investigate the risks associated with this intention since the global financial crisis in 2008. More specifically, we consider who has moved into homeownership and who has moved out of it and the reasons for having done so. We conclude that, in the initial phase in 2008 (because of increased interest rates), low-income black respondents had been more likely either to redeem their mortgages or to move out of homeownership and into rental housing. Yet, as the global financial crisis resulted in the South African recession in the second semester of 2009 and led to job losses, the negative impacts were experienced irrespective of population group or of income. Highlights: Nominal property values from over R480, 000 in 2008 to 411, 000 in 2010. Average mortgage-to-property value increased from 32.4% in 2008 to 43.9% in 2010. Negative equity remained very low at 0.4%. Households paying more than 30% of their income towards a mortgage dropped considerably.